2016
DOI: 10.1021/acs.jpcc.6b02735
|View full text |Cite
|
Sign up to set email alerts
|

Ellipsometric Study on Size-Dependent Melting Point of Nanometer-Sized Indium Particles

Abstract: Size-dependent melting properties of nanometer-sized Indium particles with size ranging from 25.5 to 68.1 nm were studied by spectroscopic ellipsometry, and a critical size is found between 42.4 and 44.9 nm. The melting points of nanometer-sized Indium particles with size larger than critical size are almost the same as that of bulk indium, while no clear melting point was found for indium particles with size smaller than the critical size. A knee point defined as the average melting point was introduced to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Neyts and Bogaerts researched the melting of nano‐Ni with different particle sizes and found that the melting temperature decreases with the particle size decreasing. Similar results were also obtained by other papers . In addition, Luo et al calculated the melting enthalpy and entropy of silver nanoparticles by molecular dynamics simulation and derived that the melting enthalpy and entropy decrease with the particle size decreasing.…”
Section: Introductionsupporting
confidence: 84%
“…Neyts and Bogaerts researched the melting of nano‐Ni with different particle sizes and found that the melting temperature decreases with the particle size decreasing. Similar results were also obtained by other papers . In addition, Luo et al calculated the melting enthalpy and entropy of silver nanoparticles by molecular dynamics simulation and derived that the melting enthalpy and entropy decrease with the particle size decreasing.…”
Section: Introductionsupporting
confidence: 84%
“…Separately, the melting point of bulk In is well above room temperature ( T m = 156.6 °C), but T m for In nanoparticles can be greatly suppressed. Values as low as T m = 25 °C have been documented for In nanoparticles with radii ( r ) = 20 nm . In nanoparticles on this size scale (Figure d) consistently did not exhibit any electron diffraction patterns when probed by selected area electron diffraction measurements (Figure e).…”
Section: Resultsmentioning
confidence: 74%
“…Values as low as T m = 25 °C have been documented for In nanoparticles with radii (r) = 20 nm. 30 In nanoparticles on this size scale (Figure 1d) consistently did not exhibit any electron diffraction patterns when probed by selected area electron diffraction measurements (Figure 1e). For reference, In nanoparticles larger than this critical threshold regularly exhibited diffraction patterns consistent with solid, crystalline In in the liquid TEM holder.…”
Section: Resultsmentioning
confidence: 95%
“…And there is a large drop in decomposition temperature for NiS 2 -80 h. The performance of the material would become very different when the particle size reduces to nanodimension, and it would cause a dramatic performance drop in the thermal properties. [39][40][41] In addition, thermogravimetric (TG) measurement shows poor repeatability. It can be partially attributed to the increase in surface energy.…”
Section: Resultsmentioning
confidence: 99%